Functioning of Directive Speech Acts in Modern German Linguistic Culture - Аdamova, H.; Аdamova, Hanna; Адамова, Ганна; Адамова, Ганна Володимирівна; Yevtimova, Diana; Євтімова, Діана; Plokhotna, Valeriia; Плохотна, Валерія; Zahura, Oksana; Загура, Оксана; Chernenko, Tetiana; Черненко, Тетяна (My University, 2022)
The speakers have a large amount of personal freedom when expressing their opinions in German. In general, Germans do not feel the need to say what you should or should not do/have in a direct manner. This can be seen through many different types of linguistic behaviors such as mimicking and directive speech acts (DSAs). The DSAs are called directive, because they often include an order or command in the speaker's words. The way how people use these DSAs varies in German culture depending on situational factors and social norms. The development of the linguistic culture in Germany, i.e., change in attitudes toward language use, has made directive speech acts more and more acceptable over time. This is illustrated by a comparison of two representative surveys conducted twenty years apart. The first representative study on directive speech acts focuses on directives addressed to learners of German as a foreign language, while the other deals with directives addressed to tourists visiting Germany.
Функціонування директивних мовленнєвих актів у сучасній німецькій мовній культурі
Аdamova H. Functioning of Directive Speech Acts in Modern German Linguistic Culture // Hanna Аdamova, Diana Yevtimova, Valeriia Plokhotna, Oksana Zahura, Tetiana Chernenko // World Journal of English Language. – 2022. – Vol. 12, № 8. – P. 212-218.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; directive speech acts; modern german linguistic culture; DSAs; German directive speech acts; combining imperatives; upward and downward polite requests; linguistic interference; language etiquette; директивні мовленнєві дії; сучасна німецька лінгвістична культура; ДМД; німецькі директивні мовленнєві дії; комбінування імперативів; нагору і низхідні ввічливі прохання; мовне втручання; мовний етикет